Consumption inductors of displacement modes linked to ride-hailing in Brazil - Violin, Fábio Luciano [UNESP] (FapUNIFESP (SciELO), 2022)
The study proposed to survey the consumption inducers related to displacement on demand in Brazil and had 3425 interviews whose data were submitted to exploratory and confirmatory factor analysis using the IBM SPSS Statistics software. In order to have robustness in the results measured, the analysis variables relating to the country's reality were designed through a review of the state of the art and the design of the supply incidence points. Six variables underlying the consumption decision-making process, based on the technological aspect of supply and marked by the utilitarian sense of use, emerged from the research. As theoretical-practical implications, the results corroborate international research linking consumption to the aspect of personal interest to the detriment of the common good and socio-environmental concerns pointed out by the first studies related to the theme. In this way, advances in the field of knowledge are indicated by highlighting the impacts of convenience, technology and individualism in consumption. The study is innovative because it outlines the indicators of consumption direction, indicating trends to be observed by public managers and private organizations, in contrast to studies on the same theme whose observation base is restricted to one location or even region.
Indutores de consumo de modais de deslocamento vinculadas ao ride-hailing no Brasil
Keywords: Sharing Economy; Transportation Network Companies; Use Motivators